Multipole Mixing Ratios of Gamma Transitions From Level 26 Mg Populated in 23Na (a, py) 26 Mg Reaction Using a2 — Ratio Method. - Saied, B. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
The 8 - mixing ratios of 7 - transitions from levels of 26 Mg populated in 23 Na (a, py)26Mg reaction are calculated using a2 — ratio method for the first time in the case of two mixed y - transitions from the same initial level. The results obtained have been compared with 8 - values determined by other methods. The comparison shows that the agreement is excellent. This confirms the validity of this method in calculating the 6 - values of such 7 - transitions.